Spring Mix—An Emerging Crop for Florida - Santiago Rosaro; Alan L. Wright; David D. Sui; Nikol Havranek; Yigang Luo (EDIS)
SL323, a 3-page illustrated fact sheet by Santiago Rosaro, Alan L. Wright, David D. Sui, Nikol Havranek, and Yigang Luo, describes the components of spring mix, explains the reasons why consumers are looking for these mixes, and why growers in the Everglades Agricultural Area of Florida are producing them. Published by the UF Department of Soil and Water Science, June 2010.